Emilio Villa: a phonetic reading of Capogrossi's Surfaces (L'uomo nero. Materiali per una storia delle arti della modernità, 2022)
In the catalogue of the solo show by Giuseppe Capogrossi at L’Attico Gallery in Rome (10-30 March 1962) the poet and art critic Emilio Villa published two texts: the first one, written for the exhibition, included a second part wrote by Villa in Latin in the earlier ‘50s; the second one, dated September 1953, was written in French; both were conceived as phonetic interpretation of Capogrossi’s signs.The essay analyzed how Villa verbally and visually re-created the sign framework by Capogrossi, by sourcing several semantic fields, and pointed out the archaic and primitive visual sources which he identified in artist’s work, and that sparked interest of artists and critics at the end of ‘40s and beginning of ‘50s, in Rome, close to Origine Foundation and “Arti Visive” magazine.
Keywords: XX c. Italian Art; Giuseppe Capogrossi; Emilio Villa